Efficiency of phosphorus sources and rates for alfalfa and centrosema cultivated in an Yellow Latosol (Oxisol) - Moreira, Adônis; Malavolta, Eurípedes; Moraes, Larissa Alexandra Cardoso (Pesquisa Agropecuaria Brasileira, 2002)
A greenhouse experiment was carried out to evaluate the efficiency of phosphorus sources and rates for alfalfa and centrosema in an dystrophic Yellow Latosol (Oxisol). A completely randomized design in a 4x4 factorial was used: four sources of P (triple superphosphate, Yoorin magnesium thermophosphate, Arad rock phosphate, and North Caroline rock phosphate) and four rates of P (0, 50, 100 and 200 mg kg-1) with three replicates. Six harvests were made. The efficiency of the phosphatic fertilizers was evaluated by the methods: Index of Agronomic Efficiency, Triple Superphosphate Equivalent, and Efficiency Index. Recovered P was evaluated by the Mehlich 1, Mehlich 3 and ion-exchange resin methods. The best Index of Agronomic Efficiency and Triple Superphosphate Equivalent were obtained for Yoorin magnesium thermophosphate. The Efficiency Index values were higher for centrosema than for alfalfa. When sequence harvest is used, the dry matter production obtained with the natural reactive phosphates tends to match the production obtained with more soluble sources. Yoorin magnesium thermophosphate increased, whereas triple superphosphate decreased soil pH; the rock phosphate had neutral reaction.